Experimental Study of the Effect of Octane Number on the - Raed R. Jasem (Tikrit Journal of Engineering Sciences, 2013)
The experiments had been carried out using two stroke, single cylinder type (TD113), with compression ratio of (7.3:1) Coupled to hydraulic dynamometer type (TD115).           The results showed that there is  enhancement   of the engine  performance  with increasing octane number. This appears clearly when comparing the results of performance with fuel of 75 and 95 octane number. The torque increases 10% at speed of 2750 RPM. The break power also increases 18% when the octane number changed from 75 to 95 at 3000 RPM of engine speed. The same change in octane number will increase the thermal efficiency by 9% at 2300 RPM of engine speed. The break specific fuel consumption decreases at the same ratio of thermal efficiency 9% but at 2400 RPM. The less fuel consumption happens at 2400 RPM for octane number 95.